Analysis of Allocation of Fulfillment, Use, and Factors Influencing the Need for Cassava Farming Funds - Sri Ayuni; Bambang Sumantri; Ellys Yuliarti (AGRITROPICA : Journal of Agricultural Sciences, 2022)
There is a lot of uncertainty in farming, such as farming funds using the results of previous agriculture; if it is not sufficient, farmers will make loans or use their assets. The long cassava production process, one year, only produced once, so for business sustainability, this cassava farming needs to be studied further. This study will see how the use, fulfillment, and factors affect the need for funds in cassava farming in South Abung District. The research location was determined purposively, and 153 farmers were selected using purposive random sampling. The analysis used is descriptive and Multiple Linear Regression. This study indicates four sources of funding for cassava farming: sources from own funds, loans to relatives and friends, intermediaries, and KUR. The funds owned by cassava farmers are allocated to buy seeds, fertilizers, pesticides, pay for labor, land taxes, and equipment depreciation. The factors that significantly influence the need for funds for cassava farming at the 95% confidence level are land area, seeds, fertilizers, and labor.